2018
DOI: 10.1259/bjr.20170453
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for radiation pneumonitis after stereotactic radiation therapy for lung tumours: clinical usefulness of the planning target volume to total lung volume ratio

Abstract: PTV/Lung is a good predictor of symptomatic RP after SRT. Advances in knowledge: The cases with high PTV/Lung should be carefully monitored with caution for the occurrence of RP after SRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…The risk factors for radiation pneumonitis have been reported to include the timing and schedule of RT sessions, the mean lung dose, the target volume and dose, pre-existing lung disease, and circulating cytokines. [22][23][24] The risk factors for immunotherapy-related pneumonitis have not been defined; however, suggestions have included active smoking, which we were unable to confirm in our study. 25 Little is known about which risk factors increase the likelihood of irAEs overall and pneumonitis in particular, and what effect irAEs might have on survival.…”
Section: Discussionmentioning
confidence: 67%
“…The risk factors for radiation pneumonitis have been reported to include the timing and schedule of RT sessions, the mean lung dose, the target volume and dose, pre-existing lung disease, and circulating cytokines. [22][23][24] The risk factors for immunotherapy-related pneumonitis have not been defined; however, suggestions have included active smoking, which we were unable to confirm in our study. 25 Little is known about which risk factors increase the likelihood of irAEs overall and pneumonitis in particular, and what effect irAEs might have on survival.…”
Section: Discussionmentioning
confidence: 67%
“…PTV/lung volume ratio has been shown a reliable factor for predicting lung dose [ 17 , 18 ]. In this study, as 6 out of 20 patients had neck lymph node metastasis, physical and EQD 2 total lung V 20 had poor linear correlations with volume ratio (LN to total lung) .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies indicated that dosimetric parameters, such as mean lung dose (MLD), V 5 , V 10 , V 20 , V 30 , V 40 , V 50 , were associated with the occurrence of RP. [22][23][24][25] All metrics above were evaluated in our study. According to the study conducted by Sheng et al, 25 total lung V 5 , V 20 , V 30 and mean dose were all correlated with grade ≥2 RP, furthermore, lung V 30 was the independent risk factor.…”
Section: Discussionmentioning
confidence: 99%